2023
DOI: 10.3390/app13042146
|View full text |Cite
|
Sign up to set email alerts
|

Dunaliella viridis TAV01: A Halotolerant, Protein-Rich Microalga from the Algarve Coast

Abstract: Tolerance to harsh environmental conditions, high growth rates and an amino acid profile adequate for human consumption are beneficial features observed in Dunaliella viridis TAV01, a novel strain isolated from a salt pond in the Algarve, Portugal. TAV01 was identified down to the species level by maximum likelihood and Bayesian phylogenetic analyses of the ribosomal internal transcribed spacers one and two regions (ITS1 and ITS-2) and was supported by ITS2 secondary structure analysis. The biochemical profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 78 publications
1
0
0
Order By: Relevance
“…(EAAI = 1.67) and Spirulina sp. (EAAI = 1.63), which are the conventional microalgal protein source [38], while it is higher than D. salina protein (EAAI = 1.53), which is also a novel microalgal protein source [18]. These results confirmed that the heterotrophic E. gracilis was a promising single-cell-protein resource with high protein content and nutritional value.…”
Section: Effect Of C/n Ratio On Protein Content Protein Yield and Ami...supporting
confidence: 56%
“…(EAAI = 1.67) and Spirulina sp. (EAAI = 1.63), which are the conventional microalgal protein source [38], while it is higher than D. salina protein (EAAI = 1.53), which is also a novel microalgal protein source [18]. These results confirmed that the heterotrophic E. gracilis was a promising single-cell-protein resource with high protein content and nutritional value.…”
Section: Effect Of C/n Ratio On Protein Content Protein Yield and Ami...supporting
confidence: 56%